2021
DOI: 10.22146/jtbb.58612
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Distribution of Sunda Pangolin (<i>Manis javanica</i> Desmarest, 1822) in Way Canguk Research Station, Bukit Barisan Selatan National Park, Lampung

Abstract: The distribution of a species can help guide the protection activities in their natural habitat. Conversely, the lack of information on this distribution makes the protection strategy of this species difficult. The research was conducted in Way Canguk Research Station, Bukit Barisan Selatan National Park from January until March 2018. The purposes of this research were to create a distribution prediction map of Sunda pangolin (Manis javanica) and estimating the environment variables that most influenced the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…This research supports the results of a previous study, which showed that the sensitivity of this species to human activity is very high, even though it can adapt to different types of forest cover in plantations or natural forests, provided food is abundant [86]. In the Bukit Barisan National Park, this species has been found to avoid areas that are disturbed by human activity, such as roads and settlements, and threats, such as poaching [87,88]. The interaction between humans and the Malayan pangolin in the GMNP was found to be low, both spatially and temporally.…”
Section: Discussionsupporting
confidence: 90%
“…This research supports the results of a previous study, which showed that the sensitivity of this species to human activity is very high, even though it can adapt to different types of forest cover in plantations or natural forests, provided food is abundant [86]. In the Bukit Barisan National Park, this species has been found to avoid areas that are disturbed by human activity, such as roads and settlements, and threats, such as poaching [87,88]. The interaction between humans and the Malayan pangolin in the GMNP was found to be low, both spatially and temporally.…”
Section: Discussionsupporting
confidence: 90%
“…However, it was not in miningaffected sites (MIN) and eruption-affected sites less than 20 years old (ERE). This result is in line with those of Lim and Ng (2008) and Anasari et al (2021), where M. javanica was discovered in several types of habitats such as near settlements, plantations/agriculture, and secondary forests. This is because the sites were close to food sources such as ants, termites, and other small insects.…”
Section: Animal Species Responsesupporting
confidence: 90%